(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of nursing interns about the implementation of the telemonitoring and post-covid rehabilitation program in a health operator of a reference hospital in the Northeast of Brazil. Methodology: This is a qualitative, descriptive study, of the experience report type, developed from the automatic reports of care of beneficiaries in post-covid discharge in the time frame from July to August 2021. Results and discussion: it was evident that post-covid patients, especially those who required prolonged hospitalization, manifested sequelae such as weight loss associated with muscle atrophy, as well as predisposition to cognitive deficits, reflecting directly in activities of daily living. Moreover, it was noticed that the Covid-19 pandemic went beyond the physical aspects of a pandemic, also reaching the psychological and emotional aspects. Conclusion: In this sense, this study enabled the understanding of the importance of monitoring the post-covid manifestations, and also contributed to the understanding of the need to use tools such as telemonitoring, aligned to health services, to strengthen the relationship between professional and patient and thus allow the promotion of holistic care.